Valentinian ethics and paraenetic discourse: determining the social function of moral exhortation in Valentinian Christianity - Tite, Philip L. (Nag Hammadi and Manichaean studies, 2009)
Introduction -- Constructing social identity through discourse : a socio-rhetorical approach for the study of Valentinian paraenesis -- Defining paraenesis I : historical phases within the academic study of paraenesis -- Defining paraenesis II : towards a functional understanding of paraenesis -- Literary aspects of paraenesis : indicators of moral exhortation from the Greco-Roman world within Valentinianism -- Two schools and the call to reconciliation : literary and social aspects of moral exhortation in the Interpretation of knowledge -- Existing in error : literary and social aspects of moral exhortation in the Gospel of truth -- Conclusion